Padé Approximants in Complex Points Revisited - Fahima Hebhoub; Lidiya Yushchenko (International Journal of Mathematics and Mathematical Sciences)
The class of complexsymmetric functions contains the Stieltjes functions. The aim of this work is to give some new results concerning the location of zeros and poles of Padé approximants using the Taylor series of functions developed in neighborhoods of complex points and their conjugate points.